Relatório de Estágio Profissional: "A Génese do docente: Como o aluno se torna professor" - Marcelo Costa Cruz (2019)
The Professional Stage is the final step of the initial formation of the teacher, where the confrontation takes place between the knowledge acquired in the course of the initial formation and the actual practice of teaching. This reflexive report is part of the second cycle of the Master's Degree in Physical Education Teaching in Basic and Secondary Education of the Faculty of Sport of the University of Porto, and is, therefore, the last step in this cycle of studies. In it, I describe my experience as a trainee student, how I fitted into the class, what difficulties I experienced when I arrived at the school, what teaching method I applied. It's also presented the school context where the professional stage took place, as well as all the experiences, learning and objectives I achieved. I also tried to explain why the class of Physical Education is very important in the academic curriculum, trying to counter the stigma surrounding it of being an irrelevant class. The methodology adopted in the realization of this report was a division in parts: the initial part is more personal and reflexive, where I describe my experiences and who I am; another, where I characterize what is the professional stage and the teaching profession; and the main part, the accomplishment of the professional stage. Overall, it is described how the I student has become the I teacher.